The table theater, a place of communication and power - Montanari, Massimo (E|C, 2020)
Eating together can say anything. If the table is a theater, it represents a place of power and communication. Starting from the story told by a 12th century chronicler who has Charlemagne and Adelchi as protagonists, the article reconstructs the political decision strategies that occur through food. Specifically, it is the story of a challenge between Charlemagne and Adelchi that takes place in the banquet hall, a topical place for ancient literature, a true "image of the world" used to represent society and power relations. In short, a place of political communication.